Single-centre case-control study investigating the association between acanthosis nigricans, insulin resistance and type 2 diabetes in a young, overweight, UK population - Neil Wright; Niamh Callanan (BMJ Publishing Group, 2022)
Objective To determine the extent to which the presence of acanthosis nigricans confers additional risk for insulin resistance, in addition to obesity alone (body mass index, BMI) within a young, overweight, UK population.Research design and methods Retrospective data were collected to compare the degree of insulin resistance within a sample of 94 young people with acanthosis nigricans, and a matched cohort of 94 participants with obesity alone. Insulin resistance was assessed by fasting glucose, fasting insulin and Homeostatic Model Assessment of insulin resistance (HOMA-IR) score (a mathematical model derived to measure insulin resistance).Results The acanthotic and control group were well matched for age, BMI, BMI SDS and sex, although the groups were not matched for ethnicity. The acanthotic group showed a significantly greater median fasting insulin (215 pmol/L), mean fasting glucose (4.7 mmol/L) and median HOMA-IR score (6.4), compared with the control group (126 pmol/L, 4.5 mmol/L and 3.7, respectively). The presence of acanthosis nigricans as an indicator of insulin resistance was found to have a positive predictive value of 81% (within this study population).Conclusion Individuals with both acanthosis nigricans and obesity had significantly greater degrees of insulin resistance than individuals with obesity alone. The findings support the potential for acanthosis nigricans as a visible marker of type 2 diabetes in young people.